2001
DOI: 10.2134/agronj2001.1305
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Liming Effects on Coastal Plain Soils and Crops

Abstract: quirement, but crops, acidic fertilizers, and nutrient removal are factors. Most soils in the southern Coastal Plain need liming; however, Subsoil acidity and infertility and their effects on plant long-term data are needed on its value and changes in soil profile pH, Ca, or Mg. Field studies with lime rates have been maintained growth, development, and yield have been researched on a Tifton soil (Plinthic Kandiudult) for 31 yr and on Pelham soil in numerous studies, which are well reviewed (Adams, (Arenic Pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 17 publications
2
24
0
1
Order By: Relevance
“…The liming residual effect varies according to the soil acidity level, rate and type of lime, soil type, management of acidic fertilizers, and cropping systems (Oliveira & Pavan, 1996;Gascho & Parker, 2001;Conyers et al, 2003;Caires et al, 2005 , and Mg 2+ contents was observed nine years after surface lime application compared with the liming initial effect. Azevedo et al (1996) found that soil pH and exchangeable Ca 2+ and Mg 2+ contents remained high, and the exchangeable Al 3+ level was low, for over 23 years after liming on a clayey soil with high organic matter content.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…The liming residual effect varies according to the soil acidity level, rate and type of lime, soil type, management of acidic fertilizers, and cropping systems (Oliveira & Pavan, 1996;Gascho & Parker, 2001;Conyers et al, 2003;Caires et al, 2005 , and Mg 2+ contents was observed nine years after surface lime application compared with the liming initial effect. Azevedo et al (1996) found that soil pH and exchangeable Ca 2+ and Mg 2+ contents remained high, and the exchangeable Al 3+ level was low, for over 23 years after liming on a clayey soil with high organic matter content.…”
Section: +mentioning
confidence: 99%
“…Surface liming ameliorates topsoil acidity in a relatively short term, but is generally slow in ame-liorating subsoil acidity, particularly in variable charge soils (Ernani et al, 2004). The movement of lime to greater depths varies according to the timing and rate of liming, soil type, surface soil pH, weather conditions, management of acidic fertilizers, and cropping systems (Oliveira & Pavan, 1996;Gascho & Parker, 2001;Conyers et al, 2003;Ernani et al, 2004;Alleoni et al, 2005;Caires et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since the lime reaction is generally limited to the layer it was applied, acidity at the subsurface layers, in case of toxic levels of aluminum and/or calcium deficiency, can compromise root penetration and plant nutrition. Results of field studies show that the movement of lime to depth varies according to timing and rates of liming, lime application forms, soil type, weather conditions, addition of acidic fertilizers, and cropping systems (Oliveira & Pavan, 1996;Caires et al, 2000;Rheinheimer et al, 2000;Gascho & Parker, 2001;Conyers et al, 2003;Pires et al, 2003;Tang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Em longo prazo já foram observados que aplicações bianuais de pequenas doses de corretivo em superfície possibilita a manutenção desse pH corrigido, mesmo em profundidade (Motta et al, 2004), fato constatado em pastagens (Brown et al, 1956), em fruticultura (Smith, 1996) e em plantio direto e convencional (Gascho & Parker, 2001).…”
Section: Resultsunclassified